Impact of different types of nitrogen and phosphorus compound fertilizers on maize yield and drip emitter clogging using secondary sewage effluent - Hao, Fengzhen; Liu, Zihui; Zhen, Zhilei; Wang, Zhen (Frontiers in Environmental Science, 2024)
Phosphorus (P) is a key nutrient for crop growth and yield. The use of drip irrigation systems to apply phosphate fertilizer may enhance the migration distance and improve usage rates. However, emitter clogging poses a substantial challenge to phosphorus drip irrigation systems. In this study, we evaluated the influences of the phosphorus fertilizer type on soil-available phosphorus (P), plant growth, yield, and drip emitter clogging. Experiments were conducted in both seasons using different phosphorus fertilizers, including urea phosphate (UP, F1), monoammonium phosphate (MAP, F2), and a combination of urea phosphate and monoammonium phosphate (UP + MAP, F3). A treatment without phosphate fertigation (F0) was used as the control. Applying phosphorus fertilizers enhanced soil-available P content, increased plant height, and improved the leaf area index (LAI) to a larger extent than those without P fertilizer. This promoted photosynthesis and increased the dry matter mass, plant P and N uptake, and aboveground plant biomass. The maximum yield of 14,764.2 and 14,778.2 kg ha−1 was obtained under urea phosphate (F1) and monoammonium phosphate (F2) in 2022 and 2023 seasons, respectively. Phosphorus fertilization changes the composition and diversity of bacterial and fungal communities in the emitter biofilm. Urea phosphate and monoammonium phosphate increased the abundance of Proteobacteria and decreased the abundance of Acidobacteriota. Acidobacteriota was strongly positively correlated with extracellular protein, whereas Proteobacteria was negatively correlated with extracellular polysaccharides, extracellular protein, and extracellular polymer. The content of extracellular polymer and solid particles decreased by 30.1%–42.0% and 39.8%–79.7%, respectively, inducing a higher relative emitter discharge for the treatment with phosphorus fertilizers. Acidic phosphorus fertilizers, such as urea phosphate and monoammonium phosphate, can maintain the high performance of drip irrigation and produce high crop yield.